Association between psychosocial well-being and problematic social media use among Finnish young adults: A cross-sectional study - Hylkilä K.; Männikkö N.; Castrén Sari; Mustonen T.; Peltonen A.; Konttila J.; Männistö M.; Kääriäinen M. (ELSEVIER, 2025)
The aim of the study was to identify associations between problematic social media use (PSMU), type of internet activity, various background factors, psychosocial factors (mood, fear of missing out, need to belong, social relationships) and the COVID-19-pandemic's impacts on social media use among young adults in Finland. Data were collected from 381 young adults aged 18-35 (M = 26.01; SD = 4.55) in Finland through a web-based survey conducted during the autumn of 2020. PSMU was identified using the Bergen Social Media Addiction Scale. Nine types of social media platform used were considered. Information about health-related factors was assessed using Beck Depression Inventory scale and a further single question. Social factors were measured using the Fear of Missing Out scale, the Single Item Need to Belong scale, and social engagement scale. 9.8 % of participants were found to exhibit PSMU. Younger people and women were more prone to PSMU. Social networking sites were the most used platform and were more strongly related to PSMU. Social media engagement, depression, fear of missing out and the effects of the pandemic on social media use were all positively and significantly associated with PSMU. These results may facilitate the development of guidelines for healthy social media use, and early detection of PSMU.